A New Runway for Journalists: On the Intentions of Journalists to Start Social Enterprises - Huei-Ching Liu; Ching Yin Ip; Chaoyun Liang (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Journalists have been facing a variety of challenges and are even being laid oﬀ in the face of changing media ecosystems in the age of digital convergence. Sharing similar characteristcs with entrepreneurs, numerous journalists have worked together to develop social enterprises, ataining social change through business approaches. The present study explores the intentons of former and current journalists to establish social enterprises, using questonnaires focused on personality traits, creatvity, and social capital. Results reveal that creatvity was found to have a signifcant inﬂuence on the social entrepreneurial intentons of journalists, as does having higher bridgingtype social capital.